Left ventricular dyssynchrony as marker of early dysfunction in premature ventricular contraction-induced cardiomyopathy - Kowlgi, Gurukripa N.; Tan, Alex Y.; Kaszala, Karoly; Kontos, Michael C.; Lozano, Pedro; Ellenbogen, Kenneth A.; Huizar, Jose F. (Frontiers in Cardiovascular Medicine, 2022)
Background: Strain imaging has been suggested as a tool to detect early left ventricular (LV) dysfunction due to frequent premature ventricular contractions (PVCs) in patients with preserved LV ejection fraction (EF). However, the progression of intraventricular dyssynchrony (IVD), radial, and circumferential strain (RS, CS) in PVC-cardiomyopathy (CM) are unknown. The aim of this study was to elucidate the progression patterns of CS, IVD, and electro-mechanical latency (EML) in PVC-CM. Methods and Results: Pacemakers were implanted in 20 canines to reproduce ventricular bigeminy at 200ms (PVCs n=11) for 12 weeks and compared to a sham group (n=9). We obtained echocardiograms at baseline, 4-, 8- and 12-weeks. RS and CS were obtained at the LV mid-cavitary level. IVD was defined as the time between the earliest and latest peak RS. EML was defined as the time between the onset of QRS and the earliest peak RS. LVEF (62±5 to 42±7%, p<0.01), CS (-18±3 to -12±3, p<0.01), and EML (219±37 to 283±46ms, p=0.02) changed significantly in the PVC group. Peak CS (-18±3 to -14±4, p =0.02) and IVD (49±31 to 122±103, p=0.05) had a significant change at 4-weeks despite preserved LVEF (51±5%). IVD normalized while EML increased at weeks 8 and 12. Conclusions: Our findings consolidate the existing theory that changes in strain precede changes in LVEF in PVC-CM. While IVD becomes abnormal early in the development of PVC-CM, it pseudo-normalizes at advanced stages due to further increases in EML suggestive of cardiac contractility remodeling. These findings are consistent with recent published data where abnormal LV mechanics could be part of a substrate that can predispose to worse outcome in PVC-Cardiomyopathy.